PENDIRIAN BANGUNAN DI SEPANJANG SEPADAN SUNGAI KARANG MUMUS BERDASARKAN PERATURAN DAERAH NOMOR 2 TAHUN 2014 TENTANG RENCANA TATA RUANG WILAYAH KOTA SAMARINDA - Rudi Hartono (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTThe purpose of this study was to find out clearly about the establishment of buildings along the Karang Mumus River border based on Regional Regulation No. 2 of 2014 concerning the Samarinda City Spatial Plan and aimed to find out the obstacles that arise in controlling buildings around the Karang Mumus River as well as resolution efforts. This research is a type of descriptive research and when viewed from its objectives, including empirical legal research. The type of data used is primary data sourced from the North Samarinda Sub-District which directly handles the communities around the river Mumus and secondary data obtained from library materials and regulations relating to the thesis title. Data collection techniques used are done by library research. Data analysis used is qualitative analysis, where data collected will be analyzed through three stages, namely reducing data, presenting data, and drawing conclusions. From the results of the study, it can be concluded that the condition of the Karang Mumus River has decreased both in terms of water quality, the physical condition of the river and its density so that it cannot function as a flood controller in the city area and as a supplier of Mahakam River water. Whereas the guidance for regulation has been regulated in Perda Number 12 of 2014 concerning Samarinda City Spatial Plan 2014 to 2034. The mechanism for the control of illegal buildings around the Karang Mumus River is to include socialization by inviting every landlord, land, or landowner, clean-action clean riverside buildings, move people around the river, demolish all new buildings without IMB, do plaster and give green open space. Keywords: Border, Mumus Coral River, Building